Bioavailability and Bioaccumulation of Heavy Metals in Soil-crop System (Brassica rapa var. Parachinensis and Brassica rapa subsp. Chinensis) and Health Risk Assessment - Thi Ha Nhung, Pham; Thi Mai Lan, Tran (VNU Journal of Science: Earth and Environmental Sciences, 2025)
In farmland, especially in the high-quality production region, although smaller quantities of agrochemicals are applied compared to conventional farming, the repeated use of chemical fertilizers and other organic amendments can increase the accumulation of heavy metals (HMs) in soils and plants and raise human health risks for consumers. Our study provides a detailed overview of the status of soils, the soil-crop transfer, and health risks of HMs (Cr, Cu, Zn, Ni, Pb, and Cd) in a vegetable planting region (with the two studied Brassica species: Brassica rapa var. Parachinensis and Brassica rapa subsp. Chinensis ), in Me Linh commune, Hanoi, Vietnam. Soil contamination assessment indicates a non-HM pollution. However, the total and bioavailable fractions of HMs can exert an impact on HM bioaccumulation tendencies in vegetables. Although low transfer factors and no significant bioaccumulation of HMs in studied vegetables are observed, the high levels of Pb (more than twice as high as the permissible FAO/WHO standards), Cr, and Cd (almost reach the standards of the FAO/WHO) in the vegetables imply potential impact on product quality and human health, especially for children. The calculated Hazard Indexes (HIs) based on total HM contents in vegetables for adults are less than 1, indicating no elevated health risk. Meanwhile, the HM-related health risk assessment indicates potentially adverse health effects (HI = 6.35 for Brassica rapa var. Parachinensis and HI = 7.85 for Brassica rapa subsp. Chinensis ) for children. Total Cr and Pb are the major contributors to the HI in both vegetables. Overall, an understanding of the potential enrichment of HMs in soils and vegetables can contribute to the safe and environmentally sustainable agriculture.